The Effect of chlorine on giardia cyst destruction isolated from different water sources in Maysan province - Al-Saad, Rasha (International Journal of Scientific World, 2016)
G. lamblia was a binucleate flagellated protozoan parasite that infected the upper intestinal tract of human and many animal species. Giardiasis was the most frequently diagnosed water borne disease and the major public health concern of water utilities in the developed and developing nations. Water is an important vehicle for the transmission of Giardia to human and mammals. For identified the effect of chlorine on Giardia cyst. To detect viability of cyst in different chlorine concentration. To determine the threshold level of chlorine concentration that caused cyst destruction. Measure the pH, chlorine concentration, filtration processes and examined by zinc sulfate centrifugal flotation technique using. 50% of samples contain Giardia cysts which are untreated water sources. Cyst viability differs in different chlorine concentration in different period of time extend from few hours to more than twenty days. The extreme chlorine concentration which caused cyst destruction in hours is 1.5 mg/L.